2010
DOI: 10.1016/j.matchar.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of SiC crystals growth on {100} and {111} diamond surfaces upon microwave heating

Abstract: The subject of this work is focused on characterization of the microstructures and orientations of SiC crystals synthesized in diamond-SiC-Si composites using reactive microwave sintering. The SiC crystals grown on the surfaces of diamonds have either shapes of cubes or hexagonal prisms, dependent on crystallographic orientation of diamond. The selection of a specified plane in diamond lattice for the TEM investigations IntroductionDiamond-SiC composites are considered one of the most promising materials for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Our previous works have demonstrated that microwave synthesis offers several advantages, such as reduced time, temperature, and energy costs during the synthesis process [18][19][20][21][22]. Additionally, the application of microwave energy to radio-absorbing materials, by means of the ponderomotive effect and electrodiffusion, enhances the characteristics of the phosphors [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous works have demonstrated that microwave synthesis offers several advantages, such as reduced time, temperature, and energy costs during the synthesis process [18][19][20][21][22]. Additionally, the application of microwave energy to radio-absorbing materials, by means of the ponderomotive effect and electrodiffusion, enhances the characteristics of the phosphors [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Very little work can be found in the literature on this topic. For instance, some works present the formation of SiC on top of diamond by the reaction of liquid silicon with diamond [1,2] or by the interaction between silicon and diamond under high pressure [3,4]. More recently, some of the present authors tried growing SiC on diamond by vapor liquid solid (VLS) transport but the deposit was polycrystalline [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it can be an alternative to improve local technological problems as ohmic contacts as Al/Si [2,3], Au/Ta [4], or Mo [5]. Nevertheless, just a few authors have studied SiC growth on diamond [6,7] most probably due to the difficulties related to this heterosystem. One of the main reasons is that diamond, as substrate, usually generates rough interface at the nanometric scale [8] due the difficulty of polishing diamond.…”
mentioning
confidence: 99%